Semi-Autogenous Grinding Model Based on Effective Grinding Rate and Three Stages Internal Classification – Part I - Magne-Ortega, L (Elsevier Ltd, 2020)
From the development of a semi-autogenous grinding model based on effective grinding rates and internal classification presented during the nineties (Magne et al., 1995) the state of the art of the mathematical structure of this model was updated, presenting the development of each subprocess from the inside of the mill in detail, considering grinding, internal classification, and mass transport. The developed model was used to demonstrate its predictive capacity using results from SAG pilot tests on copper ores. After applying the model, the ability to replicate the results obtained for size distributions of internal load, product, and the total filling level was demonstrated. This article presents, from a simplified approach and strongly based on the observation of the experimental data obtained at pilot scale, the first approach and details of how to use the model, being an alternative to the current state of the art. © 2020 Elsevier Ltd